2016
DOI: 10.1080/10428194.2016.1180685
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of response and survival in patients with relapsed and refractory multiple myeloma treated with pomalidomide plus low-dose dexamethasone in the MM-003 trial randomized phase III trial (NIMBUS)

Abstract: Relapsed/refractory multiple myeloma (RRMM) patients have poor overall survival (OS). Pomalidomide plus low-dose dexamethasone (POM + LoDEX) significantly extends OS in RRMM vs. high-dose dexamethasone. Survival of patients with stable disease (SD) was compared to patients with progressive disease (PD) or ≥ partial response (≥PR) at cycles (C) 3, 5, and 7. Among 302 patients randomized to POM + LoDEX, at C3 19.2% achieved ≥ PR, 38.4% SD, and 14.6% PD. Patients with SD at C3 (17.4%) and C5 (13.6%) showed improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
4
2
0
Order By: Relevance
“…As an encouraging result, the median OS in responders was not achieved after a median follow‐up of 28.0 months. As recently highlighted in data from the MM‐003 trial, we confirmed the absence of significant differences between response or stabilization and OS following pomalidomide initiation. Thus, a pomalidomide‐dexamethasone regimen should be a standard treatment after lenalidomide and bortezomib, including in patients with stable disease.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As an encouraging result, the median OS in responders was not achieved after a median follow‐up of 28.0 months. As recently highlighted in data from the MM‐003 trial, we confirmed the absence of significant differences between response or stabilization and OS following pomalidomide initiation. Thus, a pomalidomide‐dexamethasone regimen should be a standard treatment after lenalidomide and bortezomib, including in patients with stable disease.…”
Section: Discussionsupporting
confidence: 86%
“…As recently highlighted in data from the MM-003 trial,17 we confirmed the absence of significant differences between response or stabilization and OS following pomalidomide initiation. In patients who respond to pomalidomide at 3 months, the duration of response exceeded 14 months in 50% of the patients.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Importantly, patients who achieved SD still appeared to derive a survival benefit with an OS of 13·1 vs. 3·6 months in those with PD. Post hoc analysis of the MM‐003 trial data has also shown this relationship between depth of response and survival (San Miguel et al , ; Moreau et al , ). In our cohort, patients with sustained disease response of at least 4 months had an estimated survival of nearly 2 years, suggesting that achieving disease stability increases the opportunity to receive further treatment at progression.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, patients with SD at the start of cycles 3, 5 and 7 showed no significant difference in OS than responding patients at the same time points [19]. The STRATUS study assessed safety and efficacy of pomalidomide (4 mg daily 21/28) + low-dose dexamethasone in the largest cohort to date of RRMM patients (N = 682) failing treatment with bortezomib and lenalidomide.…”
Section: Phase III Studiesmentioning
confidence: 99%